Strategi Manajemen Pendidikan untuk Meningkatkan Minat Membaca Siswa Sekolah Dasar Negeri 145 Palembang - Emilia, Emilia; Ahyani, Nur; Nurlina, Nurlina (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to describe the Educational Management Strategy to Increase Students' Interest in Reading at State Primary School 145 Palembang. This type of research is descriptive qualitative research. Data collection tools use documentation, interviews, observation and literature review. Data analysis uses descriptive analysis. The results of the research show that the management strategy for increasing students' interest in reading at SD Negeri 145 Palembang is implemented by planning and formulating programs to increase students' interest in reading, reading infrastructure such as libraries and reading corners at SD Negeri 145 Palembang. The obstacles faced are related to the fulfillment of library and corner facilities. school reading, student interests and training and workshops related to library management and school reading corners. The solution taken was to invite the school committee to take an active role and encourage all school members to take part in activities to increase students' reading interest at SD Negeri 145 Palembang.